Highly elevated levels, infant dietary exposure and health risks of medium-chain chlorinated paraffins in breast milk from China: Comparison with short-chain chlorinated paraffins. (15th June 2021) - Xu, Chi; Wang, Kunran; Gao, Lirong; Zheng, Minghui; Li, Jingguang; Zhang, Lei; Wu, Yongning; Qiao, Lin; Huang, Di; Wang, Shuang; Li, Da
Abstract: Short-chain chlorinated paraffins (SCCPs) are persistent organic pollutants which are toxic to human. Median-chain chlorinated paraffins (MCCPs) have similar toxicity to SCCPs. The productions of chlorinated paraffins (CPs) in China were 1 million tons in 2013 and remained high after that, which may lead to high risks for human exposure to CPs. To investigate temporal trends and health risks of SCCPs and MCCPs in breast milk in China, samples ( n = 2020) were collected from urban and rural areas of 11 Chinese provinces in 2017 and mixed into 42 pooled samples. SCCPs and MCCPs were analyzed by two-dimensional gas chromatography with electron-capture negative-ionization mass spectrometry (GC × GC-ECNI-MS). The MCCP concentrations (median (range)) were 472 (94–1714) and 567 (211–1089) ng g −1 lipid in urban and rural areas, respectively, which showed continuously rapidly increasing during 2007–2017. The SCCP concentrations (median (range)) were 393 (131–808) and 525 (139–1543) ng g −1 lipid in urban and rural areas, respectively. The results showed SCCP levels decreased in urban areas between 2007 and 2017. Significant increases in MCCP/SCCP ratios might arise from extensive manufacturing and use of MCCPs. The median estimated dietary intake via breast milk in urban and rural samples were 1230 and 2510 ng kg −1 d −1, respectively, for SCCPs and 2150 and 1890 ng kg −1 d −1, respectively, for MCCPs. Preliminarily risk assessment showed that SCCPs posed a significant health risk to infants via breastfeeding. The high MCCP levels should also be of concern because of continuous growth and negative effect on infants. Correspondence analysis indicated congeners with higher carbon and chlorine numbers in dietary tend to accumulate in breast milk. Graphical abstract: Image 1 Highlights: Temporal trends of SCCPs and MCCPs in Chinese breast milk were analyzed. The MCCP levels were continuously rapidly increasing, exceeding SCCPs. The health risk of infants exposure to SCCPs and MCCPs were assessed. MCCPs need more attentions because of elevated levels and harmful to infants. Congeners with high carbon and chlorine atoms tend to accumulate in human body. Abstract : SCCP levels in breast milks declined in urban areas, while MCCP levels increased continuously in urban and rural areas in China from 2007 to 2017.